How sleep deprivation and academic stress shape statistical achievement: Evidence of academic resilience in undergraduate learners - Pramesti, Getut; Rohman, Rifki Arifur; Cahyarani, Sanggita Nariswari (Jurnal Elemen, 2025)
This study addresses a gap in the literature concerning the combined influence of stress and sleep duration on academic performance, particularly in demanding mathematics courses like Basic Statistics. Among mathematics education students—who rely heavily on concentration and logical reasoning—stress and poor sleep may significantly affect learning outcomes. Conducted at a state university in Surakarta, Indonesia, the research aimed to examine the associations between perceived stress, sleep duration, and course performance in 45 first-semester students who had completed Basic Statistics. A non-parametric quantitative design was used, with data gathered via the Perceived Stress Scale (PSS-10), a sleep duration questionnaire, and final course grades. Analyses employed chi-square tests and correspondence analysis. While no statistically significant relationships emerged, the correspondence analysis revealed intriguing proximity patterns: moderate-to-high stress and short-to-adequate sleep categories clustered near higher performance, hinting at possible nonlinear or adaptive effects. These findings, though preliminary, suggest that optimal—not minimal—stress and sufficient sleep may support academic achievement. The study underscores the need for expanded research with larger, more diverse samples to better understand these complex dynamics and inform holistic student support strategies in mathematics education.